Effect of different coupling agents in covalent enzyme immobilization on kenaf micro fibre (pdf author Ng Lin Cieh) - Ng, Lin Cieh (2018)
Enzyme immobilization by covalent binding is a technique that localizes the enzymes on a support material through the formation of covalent bonds, with retained catalytic activity. Covalent immobilization is popular for minimizing leaching of the immobilized enzymes. Therefore, using covalently immobilized enzymes enables repeated uses of the biocatalyst. It also allows easier separation between the products and the immobilized enzymes. However, many conventional support matrixes used for enzyme immobilization requires high cost. This causes the use of immobilized enzymes in industries to be less preferable. To solve this problem, researches are needed to find out alternative support materials which are more economical for industrial applications. In order to ensure the optimum performance of the immobilized enzymes in industrial operations, it is also required to study the effect of coupling agents (spacer arms and ligands) on the properties of the immobilized enzymes. Hence the objectives in this research are to study the potential of bleached kenaf bast micro fibre as the support matrix for covalent immobilization of cyclodextrin glucanotransferase (CGTase) and also to investigate the effect of different spacer arms and ligands on the properties of the immobilized CGTase. In this study, raw kenaf bast fibre was firstly bleached. After that, CGTase from Bacillus macerans was immobilized on the bleached kenaf bast micro fibre with the use of different coupling agents. Hexamethylenediamine, HMDA and Ethylenediamine, EDA were used as the spacer arms, while glutaraldehyde, GA and o-phthalaldehyde, OPA were used as the ligands. This is followed by determination of the immobilized CGTases properties such as storage stability and reusability. From the results, when 55.6 U/mL of free CGTase was initially added during immobilization, the recovered activity of immobilized CGTases are in the range of 0.16 to 0.24 U/(mg fibre). Besides, a shift in optimum temperature was also detected from 60oC (free CGTase) to 70oC (immobilized CGTases). This indicates that the thermal stability for the immobilized CGTases are higher when compared to free CGTase. For storage stability at 60oC, CGTase immobilized with ethylenediamine and o-phthalaldehyde, has retained 60% of its initial activity after 15 days of storage. This highest stability was confirmed by its lowest deactivation constant, kd (0.0361 day-1). However for reusability, CGTase immobilized using ethylenediamine and glutaraldehyde retains the highest residual activity (72.72%) after 12 cycles of batch reaction. From this study, the potential of bleached kenaf bast micro fibre has been confirmed since it can enhance the performance of all the immobilized CGTase, regardless of the coupling agents used. In addition, the present study has also proven the importance of selecting suitable coupling agents as they have different effect on the properties of the immobilized enzymes.